2003
DOI: 10.1161/01.atv.0000074146.36646.c8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral and Transdermal Estrogen Replacement Therapy on Hemostatic Variables Associated With Venous Thrombosis

Abstract: Objective-The purpose of this study was to investigate whether the effect of transdermal estrogen therapy in postmenopausal women differs from that of oral therapy with regard to resistance to activated protein C (APC), an important risk factor for venous thrombosis, and levels of related proteins, such as protein S, protein C, and prothrombin. Methods and Results-In a randomized, double-blind, placebo-controlled study, 152 healthy hysterectomized postmenopausal women received daily either placebo (nϭ49), tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 36 publications
5
73
1
5
Order By: Relevance
“…29 In addition, 2 randomized controlled trials have shown that oral but not transdermal estrogen, both combined with micronized progesterone, induced an activated protein C resistance. 30,31 Thus, hemostatic data, together with the results of the ESTHER study, suggest that transdermal estrogen combined with micronized progesterone is safe with respect to VTE risk. Similarly, recent data showing that chlormadinone acetate, a pregnane derivative, has little or no effect on blood coagulation and fibrinolysis 32 are consistent with the absence of increased VTE risk among postmenopausal women using transdermal estrogen combined with pregnane derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…29 In addition, 2 randomized controlled trials have shown that oral but not transdermal estrogen, both combined with micronized progesterone, induced an activated protein C resistance. 30,31 Thus, hemostatic data, together with the results of the ESTHER study, suggest that transdermal estrogen combined with micronized progesterone is safe with respect to VTE risk. Similarly, recent data showing that chlormadinone acetate, a pregnane derivative, has little or no effect on blood coagulation and fibrinolysis 32 are consistent with the absence of increased VTE risk among postmenopausal women using transdermal estrogen combined with pregnane derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, an acquired resistance to activated protein C has been demonstrated in users of oral estrogen, 14 but 2 randomized trials recently indicated that these results did not apply to users of transdermal estrogen. 15,16 Thus, oral estrogen may impair the balance between procoagulant factors and antithrombotic mechanisms, whereas transdermal estrogen appears to have little or no effect on hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Oral versus transdermal administration of 17b-estradiol (E 2 ) may impact differently on variables such as inflammation markers (15), lipoproteins (16), and coagulation markers (17). The pharmacological nature of the estrogen compound may be of significance too: oral administration of the synthetic compound ethinyl estradiol may have more negative effects on hemostasis than oral or transdermal E 2 (18).…”
Section: Introductionmentioning
confidence: 99%